Literature Review Audit Tata Kelola Teknologi Informasi Menggunakan Kerangka Kerja COBIT 2019 - A’yuni, Ashlih Qurota; Muhammad, Alva Hendi; Nasiri, Asro (Jurnal Informa : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
Information Technology Governance Audit is an evaluation process carried out to evaluate the level of maturity or readiness of an organization in managing information technology. Information Technology governance audit basically focuses more on IT management and its implementation to then produce evaluations and recommendations for company improvement. COBIT 2019 can be used as a framework for conducting IT governance audits. COBIT 2019 is the latest version of COBIT with various advantages, namely, flexibility and openness, novelty and relevance, has a level of adaptation to developments with the latest technology today, provides more in-depth guidance on corporate IT governance according to the needs of each company. Of the 15 articles that have been collected, there are 2 articles that really discuss the entire information technology governance audit process, and 2 articles that discuss in detail the planning of information technology governance audits. While the other 11 articles only arrive at the calculation of the level of capability, the calculation of the maturity level of information technology governance. From these findings, it is hoped that there will be better research in the future.